Evaluation of the Implementation of Balance in Protecting the Rights of Entrepreneurs, and Workers in the Job Creation Law Post-the Constitutional Court Decision Number 168/PUU-XXI/2023: ASocio-Legal Study: Evaluation of the Implementation of Balance in Protecting the Rights of Entrepreneurs, and Workers in the Job Creation Law Post-the Constitutional Court Decision Number 168/PUU-XXI/2023: ASocio-Legal Study - Hendriadi, Martin Triadmaja; Hamid, Adnan; Iriantoro, Agung; Komandoko, Kukuh (PENA LAW: International Journal of Law, 2025)
This study aims to evaluate the implementation of the balance of protecting the rights of employers and workers in Law Number 6 of 2023 concerning the Stipulation of Government Regulation instead of Law Number 2 of 2022 concerning Job Creation into Law or the Job Creation Law (hereinafter referred to as Law 6/2023) post-the Constitutional Court or Mahkamah Konstusi (MK) Decision No. 168/PUU-XXI/2023: a socio-legal study. Literature studies were conducted as a basis for answering various problems in this study. Then, data processing was carried out qualitatively. The results of this study indicate that Law 6/2023, after the Constitutional Court Decision, underlines the importance of normative workers' rights, which have an impact on legal certainty and benefits for workers. Law 6/2023) after the Constitutional Court Decision tends not to affect entrepreneurs. The evaluation results of the implementation of the Job Creation Law after the Constitutional Court Decision indicate that the issue of protecting employers' rights is crucial. Therefore, Law 6/2023, after the Constitutional Court Decision, is expected to be amended not only to address the imbalance in workers' rights but also the rights of employers. Thus, the results of this study are expected to be used by the government and the legislature to form employment laws and ensure fair implementation of the balance between protecting entrepreneurs.' and workers' rights in Law 6/2023 after the Constitutional Court Decision by the constitution, Article 27 paragraph (2), Article 28D paragraph (2), and Article 33 of the 1945 Constitution.